Nilai-nilai Multikultural dalam Pendidikan Pancasila dan Budi Pekerti di Madrasah Ibtidaiyah - Maulana Jamaludin, Gilang; Araniri, Nurudin; Nahriyah, Syafa'atun (Departement of PAI, Universitas Majalengka, 2023)
This study aims to determine multicultural values in Pancasila and Moral Education in Madrasah Ibtidaiyah. This research uses the library research method or literature review. The results obtained from this study are multicultural values in Pancasila and moral education. These values are the values of tolerance, mutual respect, respect for culture and religion, togetherness, unity, cooperation and solidarity values, these are contained in Pancasila. The results of the study can be concluded that the multicultural values contained in Pancasila and character education serve as guidelines that underlie attitudes in the nation and state. Pancasila is explored from the values, views and culture of life of the Indonesian people. In this regard, it is very important to implement Pancasila and character education in schools, bearing in mind that currently there are many phenomena that erode Pancasila values to the nation's next generation.